Water Dispute between India and Pakistan: An Analysis (Journal of Asian Development Studies, 2024)
Water disputes between India and Pakistan revolve around river basins and are rooted in theregion's geography, shared history, and culture. Tensions about water issues in South Asia haveescalated significantly due to the deteriorating relations between Pakistan and India, stemmingfrom India's inequitable practices in water allocation. Pakistan and India engaged in conflictover the Indus basin rather than negotiating the 1960 Indus Waters Treaty, which both nationshave upheld for over 63 years despite two wars and the nuclear age. The water issue betweenIndia and Pakistan is a protracted conflict that worsens each day. The presence of nucleararsenals in the region has added to the volatility of water disputes. This situation requires thatwater conflicts between Pakistan and India be studied, and possible alternate options andstrategies may be explored to lessen the intensity of the water conflicts between Pakistan andIndia. Thus, the study examined the water disputes between the two countries. The hydrohegemony framework was put in to understand the water disputes between India and Pakistanbecause India lands in the graph of negative hegemony. The study suggests that both countries'water management should have feasible regional arrangements